Come to the Street and the Free Brazil Movement in the Context of the Parliamentary Coup in Brazil - Oliveira, Diego Batista Rodrigues de; Machado, Eliel (Pontifícia Universidade Católica de São Paulo, 2019)
The objective of this article is to analyze from a classist perspective the Come to the Street movement and the Free Brazil Movement, two liberal and conservative social movements that emerged in the context of the parliamentary coup that removed President Dilma Rousseff of the Workers’ Party (PT) in Brazil. Because Marxism has privileged the analysis of movements tied to labor and the reproduction of the workforce, there are few analyses of liberal and conservative social movements. Through the analysis of a specific conjuncture, we seek to advance our hypothesis that fractions of the middle class organized themselves in support movements for the defense of their specific interests and/or to support hegemonic fractions within the power bloc.